Evaluating Oral Hygiene and Caries Prevalence among Deaf and Hard of Hearing Orphans at Karya Murni Orphanage in Medan - Sofyanti, Ervina; Siregar, Darmayanti; Sitanggang, Maria Novita Helen; Sitorus, Marshall Gregory; Kwan Min Fook (Dentika: Dental Journal, 2024)
Access to equal oral health attention is the right of all human beings, including orphan children with hearing loss or deaf and hard of hearing (DHH) conditions. Therefore, this study aimed to determine the correlation between the level of oral hygiene and caries indexing among the sub-population of DHH orphans receiving special care at Karya Murni orphanage in Medan City. A cross-sectional design was used with non-probability sampling to select 58 orphans willing to engage in the Oral Hygiene Index-Simplified (OHI-S) and mean of Decayed, Missing, and Filled Permanent Teeth (DMFT) assessment during dental and oral cavity screening after participating in counseling activities. Furthermore, the results showed a positive correlation (p=0.007) between oral hygiene and caries, suggesting that OHI-S impacted DMFT by approximately 34.9%, with both index scores presenting proportional equivalence. There is a need to conduct regular dental health monitoring along with education on visual methods and sign language among DHH orphans. Additionally, DHH orphan caregivers should actively engage in enhancing personal health behaviors, particularly to maintain oral and dental health.